Pengaruh Cita Rasa Dan Harga Terhadap Kepuasan Pelanggan Di Rumah Makan Rasbani Selong Lombok Timur - Baiq Rina Fadilah; M. Ilhamuddin; Rahman Dayani (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The purpose of the research is to analyze the level of customer satisfaction at Rasbani Restaurant in Selong, East Lombok, which is influenced by price and taste. The data collection method implements a questionnaire survey and interviews with 100 customers of Rasbani Restaurant. Based on the results of the t-test and multiple linear regression analysis, the sig. value between customer satisfaction and taste (X1) is below 0.05, namely 0.000, which means that customer satisfaction is positively influenced by taste and the percentage of influence is 60.6%. Meanwhile, the sig. value for the correlation between customer satisfaction and price (X2) is above 0.05, namely 0.065, which means that customer satisfaction is not significantly influenced by price in a positive direction, where the percentage level of influence is 14.7%. In addition to the t-test, the F-test was also carried out and it was found that customer satisfaction as the dependent variable was simultaneously influenced by price and taste as independent variables.